Measure, Then Show: Grasping Human Evolution Through an Inquiry-Based, Data-driven Hominin Skulls Lab - Bayer, Chris N.; Luberda, Michael (PLOS ONE, 2016)
Incomprehension and denial of the theory of evolution among high school students has been observed to also occur when teachers are not equipped to deliver a compelling case also for human evolution based on fossil evidence. This paper assesses the outcomes of a novel inquiry-based paleoanthropology lab teaching human evolution to high-school students. The inquiry-based Be a Paleoanthropologist for a Day lab placed a dozen hominin skulls into the hands of high-school students. Upon measuring three variables of human evolution, students explain what they have observed and discuss findings. In the 2013/14 school year, 11 biology classes in 7 schools in the Greater New Orleans area participated in this lab. The interviewed teacher cohort unanimously agreed that the lab featuring hominin skull replicas and stimulating student inquiry was a pedagogically excellent method of delivering the subject of human evolution. First, the lab’s learning path of transforming facts to data, information to knowledge, and knowledge to acceptance empowered students to themselves execute part of the science that underpins our understanding of deep time hominin evolution. Second, although challenging, the hands-on format of the lab was accessible to high-school students, most of whom were readily able to engage the lab’s scientific process. Third, the lab’s exciting and compelling pedagogy unlocked higher order thinking skills, effectively activating the cognitive, psychomotor and affected learning domains as defined in Bloom’s taxonomy. Lastly, the lab afforded students a formative experience with a high degree of retention and epistemic depth. Further study is warranted to gauge the degree of these effects.